2017
DOI: 10.1007/s11130-017-0640-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Properties and Antioxidant Activities of Extracts from Wild Blueberries and Lingonberries

Abstract: Among Vaccinium species, blueberries (Vaccinium myrtillus L.) and lingonberries (Vaccinium vitis-idaea) are popular in the human diet. In this study, total phenolic, total flavonoid and total monomeric anthocyanin contents in the ethanol-water extracts of blueberry and lingonberry fruits grown wild in the forests in the central region of Poland were assayed. Antioxidant activities of the extracts from each plant were also evaluated for scavenging ability on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…All the data were calculated as fresh weight to better describe the content (Gu et al, 2004). , & Pyrzynska, 2017;Kim et al, 2018). The proanthocyanidins content varies a lot in different types of whole fruits, even in those belonging to the same family.…”
Section: Proanthocyanidins In Fruits and Vegetablesmentioning
confidence: 99%
“…All the data were calculated as fresh weight to better describe the content (Gu et al, 2004). , & Pyrzynska, 2017;Kim et al, 2018). The proanthocyanidins content varies a lot in different types of whole fruits, even in those belonging to the same family.…”
Section: Proanthocyanidins In Fruits and Vegetablesmentioning
confidence: 99%
“…[7,8] The effects of the genotype, growing seasons, climate conditions, ripeness, and storage conditions on the phenolic content and antioxidant activity in the blueberry fruits have been reported. [1,7,[9][10][11][12][13] Previous studies have reported that blueberries are rich in phenolics, which are greatly affected by varieties and producing regions [14,15] , and phenolic compounds, including quinic acid, chlorogenic acid, gallic acid, p-coumaric acid, caffeic acid, ferulic acid, ellagic acid, rutin, catechin, epicatechin, myricetin, quercetin, and kaempferol. [13,[16][17][18][19][20][21] The concentrations of phenolic acids and flavonols in unripe green and fully ripe fruits were high and similar, whereas the lowest levels were found in intermediately ripe fruits.…”
Section: Introductionmentioning
confidence: 99%
“…When lingonberry (Vaccinium vitis-idaea) which is grown in Poland and blueberries (Vaccinium myrtillus L.) are compared in terms of phenolic ingredients they contain, blueberries have shown more antioxidant activity. It was found that increased anthocyanin content in blueberry increased the effect of radical cleansing and antioxidant activity (8).…”
Section: D)mentioning
confidence: 99%